1963
DOI: 10.1172/jci104765
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Taste Thresholds in Normal Man and in Patients With Adrenal Cortical Insufficiency: The Role of Adrenal Cortical Steroids and of Serum Sodium Concentration

Abstract: Patients with adrenal cortical insufficiency exhibit an increased taste sensitivity for sodium chloride (NaCl) (1). Treatment with carbohydrate-active steroids returns the abnormal threshold to normal levels (1). In a variety of acute and chronic debilitating diseases, a number of them exhibiting major abnormalities of water and electrolyte metabolism, taste threshold for NaCi is comparable to that observed in healthy subjects (1). Taste thresholds for all modalities are decreased in cystic fibrosis, but they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
88
1
11

Year Published

1968
1968
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(105 citation statements)
references
References 15 publications
5
88
1
11
Order By: Relevance
“…[4][5][6] This finding may reflect observed in patients with cirrhosis, and hypomagnesemia the use of a rinsing procedure 28 rather than a dropping techwas associated with impairment of gustatory function. Alnique, 9 although the thresholds observed in our healthy volthough many patients reported that their appetites were poor unteers were comparable to values reported previously. and that they did not enjoy their food, their subjective assess-…”
Section: Healthy Volunteers and 75 Cirrhotic Patientssupporting
confidence: 90%
See 2 more Smart Citations
“…[4][5][6] This finding may reflect observed in patients with cirrhosis, and hypomagnesemia the use of a rinsing procedure 28 rather than a dropping techwas associated with impairment of gustatory function. Alnique, 9 although the thresholds observed in our healthy volthough many patients reported that their appetites were poor unteers were comparable to values reported previously. and that they did not enjoy their food, their subjective assess-…”
Section: Healthy Volunteers and 75 Cirrhotic Patientssupporting
confidence: 90%
“…No overall trends were observed context. In four studies, 4-7 for example, gustatory acuity was among healthy volunteers or patients between the taste assessed using a dropping technique 9 in which a single drop thresholds observed and the reported use of condiments and of tastant solution and two drops of distilled water are placed flavorings. in random order on the tongue and the subject is asked There were few differences in the food selections made by which, if any, of the drops taste different than water.…”
Section: Healthy Volunteers and 75 Cirrhotic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Тест был разработан Henkin R. J. et al еще в 1963г и успешно адаптирован Константиновым Е. Н. и соавт. в 1983г [8][9]. Показано, что ПВЧПС является отражением уровня потребления поваренной соли с пищей и выделения хлорида натрия с мочой и, по мере увеличения значений этих парамет ров, про-исходит повышение ПВЧПС [10].…”
unclassified
“…Превышающие его концентрации считаются высоким ПВЧПС и в настоящее время рассматриваются как дополнительный фактор риска артериальной гипертензии. Нами применялась модифицированная методика R. Henkin, в оригинальной методике применяется последовательное увеличение концентрации соли с 0,0025% до 5,12%, при этом в каждой последующей пробирке концентрация соли увеличивалась в 2 раза [9]. Однако проведенные нами серии наблюдений показали, что никто из испытуемых не ощущал вкус соли в концентрации 0,04% и все ощущали в концентрации 0,4%.…”
unclassified